Human Linguisticality and the Building Blocks of Languages - Haspelmath, Martin (Frontiers in Psychology, 2020)
This paper discusses the widely held idea that the building blocks of languages (features, categories and architectures) are part of an innate blueprint for Human Language, and notes that if one allows for convergent cultural evolution of grammatical structures, then much of the motivation for it disappears. I start by observing that human linguisticality (= the biological capacity for language) is uncontroversial, and that confusing terminology ("language faculty", "universal grammar") has often clouded the substantive issues in the past. I argue that like musicality and other biological capacities, linguisticality is best studied in a broadly comparative perspective. Comparing languages like other aspects of culture means that the comparisons are of the Greenbergian type, but many linguists have presupposed that the comparisons should be done as in chemistry, with the presupposition that the innate building blocks are also the material that individual grammars are made of. In actual fact, the structural uniqueness of languages (in lexicon, phonology and morphosyntax) leads us to prefer a Greenbergian approach to comparison, which is also more in line with the Minimalist idea that there are very few doman-specific elements of the biological capacity for language.